2000
DOI: 10.1063/1.1319995
|View full text |Cite
|
Sign up to set email alerts
|

Oriented chlorine atoms as a probe of the nonadiabatic photodissociation dynamics of molecular chlorine

Abstract: Molecular chlorine was photolyzed using circularly polarized radiation at 310 and 330 nm, and orientation moments of the chlorine-atom Cl(2 P j) photofragment distributions were measured by resonance enhanced multiphoton ionization using circularly polarized light with Doppler resolution. The product atoms were found to be strongly oriented in the laboratory as a result of both incoherent and coherent dissociation mechanisms, and the orientation moments contributed by each of these mechanisms have been separat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
87
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(91 citation statements)
references
References 32 publications
4
87
0
Order By: Relevance
“…For most of the studies undertaken to date [6,7,9,10,12,14,15], the number of interacting molecular quantum states was limited to 2-3. In these cases, the relationship between the dynamical functions and the T-matrix amplitudes and phases is straightforward and the 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 F o r P e e r R e v i e w O n l y corresponding amplitudes and phases can be relatively easily determined from experimental data; see, for example, the review paper [25].…”
Section: Analysis and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For most of the studies undertaken to date [6,7,9,10,12,14,15], the number of interacting molecular quantum states was limited to 2-3. In these cases, the relationship between the dynamical functions and the T-matrix amplitudes and phases is straightforward and the 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 F o r P e e r R e v i e w O n l y corresponding amplitudes and phases can be relatively easily determined from experimental data; see, for example, the review paper [25].…”
Section: Analysis and Resultsmentioning
confidence: 99%
“…Several experimental studies have reported measurements of such orientation and alignment parameters (generically referred to hereafter as anisotropy parameters) for photodissociation of a variety of diatomic systems (see, for example, [6][7][8][9][10][11][12][13][14][15][16]), and results have been used to infer certain non-adiabatic crossing probabilities and phase shifts [10], as well as the shapes of molecular potential energy curves [17]. Theoretical analysis by Balint-Kurti and coworkers [2,3] pointed the way to the determination of all amplitudes and phases of T-matrix elements, and illustrated the connection to anisotropy parameters by using wavepacket propagation to compute the photodissociation dynamics of HF and HCl.…”
mentioning
confidence: 99%
“…[5][6][7][8][9][10] The scattering experiments performed typically have a high collision energy ϳ500 cm −1 above the NO͑X͒ + Ar asymptote and the agreement with ab initio calculations 1,2,11 suggests that there is a good understanding of the interaction and dynamics involved, i.e., scattering from the repulsive part of the potential energy surface at these energies. Nonresonant photodissociation of the NO-Ar complex has been performed at a range of energies above the NO͑A͒ + Ar asymptote, typically 25-400 cm −1 .…”
Section: Introductionmentioning
confidence: 99%
“…26,27 The 351 nm beam was The analysis of the images was performed using BASEX. 29 Since the molecular beam originates from one point, namely the centrally-mounted molecular beam valve, each beam has an off-axis velocity component proportional to the offset of the respective hole.…”
Section: B Calibrationmentioning
confidence: 99%